2002
DOI: 10.1002/1521-3765(20020617)8:12<2650::aid-chem2650>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Basic Concepts of “Cation Pool” and “Cation Flow” Methods and Their Applications in Conventional and Combinatorial Organic Synthesis

Abstract: Current events: Nanowires of the organic semiconductor copper–tetracyanoquinodimethane (Cu–TCNQ) have been synthesized in a controlled manner and patterned on a variety of substrates by chemical vapor deposition. A cross‐point memory device based on a network of Cu–TCNQ nanowires (see picture) has been constructed that repeatedly switches electrically between two states with a conductivity difference of more than two orders of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(93 citation statements)
references
References 7 publications
1
89
0
3
Order By: Relevance
“…Yoshida et al [52,53] developed a unique ''cation-flow'' method and applied it to combinatorial organic syntheses. Carbocations play an important role in organic synthesis.…”
Section: Sequential Micro Reaction Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yoshida et al [52,53] developed a unique ''cation-flow'' method and applied it to combinatorial organic syntheses. Carbocations play an important role in organic synthesis.…”
Section: Sequential Micro Reaction Systemsmentioning
confidence: 99%
“…Schematic diagram of the ''cation-flow'' system. [52] Figure 14. An electrochemical micro-flow reactor for the ''cation-flow'' method.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…(For recent papers on organic electrosynthesis, see for example, refs [16][17][18] Electrochemical oxidation in solvents normally used in organic syntheses can be carried out by the cation pool method. [19][20][21] We have reported that the electrochemical oxidation of diaryl disulfides (ArSSAr) leads to the formation of ArS(ArSSAr) + , which can be accumulated in solution at low temperatures ( Figure 1). [22][23][24][25][26] This reaction presumably proceeds by generation of "ArS + " followed by its reaction with ArSSAr.…”
Section: Introductionmentioning
confidence: 99%